Assessment of the efficiency of the european payment system - introducing the current european snapshot - Vassalo, Maria Joana De Carvalho Figueira (2023)
This research report performs an efficiency analysis of the European digital payment system. Its characterization was performed considering the evolution from cash to digital payments and the inherent risks, drivers of change, and trends. A novel payment system efficiency index is proposed and computed, where efficiency is defined as an optimization of cost, speed, availability, security, and convenience. Comparing with other regions, the EU is generally as efficient as the average benchmark, outperforming in terms of security but underperforming in terms of convenience. Improving instant payments and implementing the Digital Euro will be crucial to overcome the existing efficiency barriers.